COVID-19 pandemic impact on primary immunization uptake - Khalid Alhusayn; Thamer Alsulaiman; Ahmed Abdulkarim; Habiba Sultana; Hussam Jnaid; Yaser Alendijani; Abdullah Alkhenizan (Journal of Family Medicine and Primary Care)
Purpose/Background: Pediatricians across the world are seeing a steep drop in the number of children coming in for appointments due to COVID-19 pandemic. To prevent outbreaks of serious diseases that pose an even greater threat to children than COVID-19, it is important that children not skip their routine vaccines. The aim of this study was to determine the impact of COVID-19 pandemic on primary immunization activities in Saudi Arabia. Settings and Design: Cross-sectional design. Methods and Material: The study was conducted at a community pediatric clinic. All parents of preschool-age children who visited the community pediatric clinics were asked to complete a self-administrated questionnaire on primary immunization uptake during the pandemic. Statistical Analysis Used: The Chi-square and Fisher’s exact test were performed to examine the demographic differences between participants who missed vaccination during the pandemic and reasons for missing the vaccination. Results: Three hundred study participants completed our questionnaire. In total, 90.6% of respondents were up to date with their vaccinations prior to the pandemic, and most respondents believed that children should be immunized at an appropriate age, it is essential for children to be fully immunized, vaccination is effective in preventing serious disease, and childhood immunization is essential during the pandemic (98.3%, 98.7%, 97.3%, and 93.7%, respectively). In total, 72.4% of respondents did not miss their vaccinations during the pandemic, while 26.6% missed vaccinations. The most common reason for missing vaccinations during the pandemic was transportation difficulty and curfew, followed by fear of contracting COVID-19 infection (40.9% and 35.5%, respectively). Those who did not believe that childhood immunization was necessary during the pandemic were more likely to miss vaccinations during the pandemic (P < 0.001). In addition, those who did not have a family member with COVID-19 infection were more likely not to miss the vaccine (P < 0.001). Moreover, those who thought taking vaccinations in a primary care setting or hospital is safe were more likely not to miss the vaccination during the pandemic (P < 0.027) and (P < 0.001). Conclusions: Significant portion of the population was affected and missed immunizations during the pandemic. The perceptions on the importance of immunization and having a family member affected with COVID-19 during the pandemic were important factors in missing immunizations. Moreover, transportation and fear of contracting COVID-19 during the curfew were also common reasons for missing immunizations during the pandemic.